The shadow that troubles the Spirit: India and the Bhagavad Gita in Hegel’s Work - Loundo, Dilip (Revista Eletrônica Estudos Hegelianos, 2023)
This essay aims to analyze the content and argumentative consistency of Hegel's critique of Indian philosophy and, more specifically, the Indian philosophies of non-duality (advaita). If it is a fact that, on balance, Hegel embraces the idea that Eastern philosophies are situated in the “infancy” of rational thought and in a condition of subservience to religion, topical but highly significant instances of his mature work reveal an openness to the possibility and admissibility of a deeper, autonomous and self-conscious rationality. For a systematic analysis of those precious instances, preference is given to the two articles jointly entitled On the Episode of the Mahabharata Known by the name Bhagavad Gita by Wilhelm von Humboldt  of 1827; and, in addition, to significant passages from the works Lectures on the Philosophy of Religion (Part II) of 1827-1831, and Philosophy of Mind of 1930. These are later writings that reflect Hegel's growing interest in the original textualities of Indian philosophy and religion, in particular the Bhagavad Gita, the Upanisads, the Yogasutra, and the Buddhist sutras (sermons).
Keywords: Indian philosophy; yoga; subjectivity; Bhagavad Gita